Kerangka garis panduan dalam proses pembangunan produk perbankan Islam di Malaysia - Mohd Sokris, Faiqah (2024)
The Islamic products and financial services are seen as having a huge potential in the financial sector and play a vital role in spurring the economy of Malaysia. Until the end of 2018, the accumulation of Islamic banking assets reached RM 916, 711.3 million, which is 31.4 percent of the total assets of the entire national banking system. With the rapid current developments of Islamic finance, banking institutions have offered various products of Islamic banking, which are generated without any standard guidelines in relation to the approach applied in most developments of Islamic products that can be adopted by every banking institution. Hence, this research is conducted to identify the approach adopted in the development of Islamic banking products. In addition, this research is carried out to analyse the methods of implementation used in the process of developing Islamic banking products. Finally, this research is aimed at developing a framework of guidelines on the Islamic banking product development. This research is a case study that uses a qualitative approach. The methodology of this research includes semi-structured interview techniques on three Shariah officers and five members of the Shariah committee of Islamic banking institutions in Malaysia. The analysis of the research data is conducted by employing the NVivo 12 software in an effort to identify the theme and sub-themes. The research results report al-hilah al-Syar’iyyah as the approach applied in the Islamic banking products. This approach has been employed in the manufacture of Islamic banking products in order to meet several requirements, such as the requirements of banking institutions, Shariah and regulators. The analysis of the following findings also reveals that said requirements are important elements in structuring Shariah-compliant Islamic banking products. This research identifies this factor as part of the implementation methods in the product development process. There are three stages of the Islamic banking product development, namely the conceptualisation of products, the development of products and the commercialisation of products. Subsequently, a framework of guidelines has been developed to be used as guidance for regulators in emphasising the crucial elements that ought to be mastered by the practitioners of Islamic banking institutions in an effort to preserve their expertise. Nevertheless, since this research is only carried out amongst Shariah officers and members of the Shariah committee of the Islamic banking institutions in Malaysia besides being limited to the al-hilah al-Syar’iyyah approach in Islamic banking, a research that includes other respondents or a research on the al-hilah al-Syar’iyyah approach in a wider context and detail is suggested as an extensive research.